Attitude towards the elderly from the staff working in the emergency wards in Lima hospitals in Lima - Ortiz Saavedra, Pedro José (2013)
Objective: To assess the emergency services personnel's attitude towards the elderly in Lima hospitals  Material and Method: The Kogan's Attitudes towards Older People Scale (KOP), validated by Sampen in Peru, was administered to healthcare workers from the Emergency Departments in three national hospitals in Lima: Cayetano Heredia (HNCH), Arzobispo Loayza (HNAL), and Hipolito Unanue (HNHU). A positive attitude towards the elderly was established if calculated scores in KOP were above 102, and a negative attitude was defined when KOP scores were 102 or lower. Results: Two hundred and thirty five healthcare workers were interviewed. Nearly half of them (45,5%) were physicians, 45,5% were nurses, and 9% were administrative personnel. The mean age of interviewees was 34 years (SD: 7,3) and 50,6% were female. A positive attitude towards the elderly was found in 97,6% of the emergency service healthcare workers in HNCH, in 95,4% in HNAL, and 98,8% in HNHU. There were no differences between the hospitals studied, and also no differences were found with respect to sex, age, position or time working in the hospital.   Conclusions: The attitude towards the elderly from healthcare workers in the Emergency Services in three National Hospitals in Lima is positive.